Fabrication and characterization of some NiZn-based ferrite multilayer inductors (MLIS) - Liew, Lucia Woan Shyan (2000)
The multilayer inductor is particularly important as a highly stable, easy to use and miniaturised component in electronic systems, such as radios, VCRs and computers. There were two main tasks in this research project, one was to make a proper preparation set-up, and the other was to measure the inductance and the reciprocal of the Q factor of the multilayer inductors produced. Layers of ferrite sheets were stacked together with silver layers in between by means of tape casting method. End metallization was applied to make contact with the inner conductors. Bulk and multilayered components of the same dimension were made to undergo parallel conventional sintering. The experimental work resulted in the complete construction of a tape-casting setup. The measured L values were in the range of 10⁻¹ to l0⁵ Henries and L fell rapidly with frequency from 1kHz to 30MHz. The energy was represented by l/Q ranged from 10⁻³ to 10 and also fell rapidly within the same frequency range.